BUY NOW PAY LATER USAGE AMONG GENERATION Z IN INDONESIA: AN INTEGRATION OF THEORY OF PLANNED BEHAVIOR AND MATERIAL VALUES THEORY - Rahmadina Oktariani; Dewi Rahmayanti; Chairil Afandy (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study aims to examine the influence of attitude toward behavior, subjective norms, perceived behavioral control, and materialism on intention to use and actual usage behavior of Buy Now Pay Later (BNPL) services among Generation Z in Indonesia, with intention as a mediating variable. Research Methodology: This study adopts a quantitative approach with an explanatory survey design. Data were collected from 255 Generation Z respondents aged 18–29 years who had used BNPL services, using purposive sampling and a structured questionnaire. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0, with bootstrapping of 5,000 subsamples. Results: Attitude, subjective norms, and perceived behavioral control positively and significantly influence both intention and BNPL usage behavior. Unexpectedly, materialism shows a significant negative effect on BNPL usage behavior, contrary to the hypothesized direction. Intention mediates the relationships of attitude and subjective norms toward BNPL usage behavior, but does not mediate the relationship of perceived behavioral control. Conclusions: This study extends TPB by demonstrating that its core constructs remain robust predictors of BNPL adoption even when materialism is introduced as a competing predictor, and by showing that materialism operates through a distinct, non-TPB mechanism that warrants further theoretical attention rather than being assumed to reinforce TPB pathways. Limitations: This study is limited to Generation Z users and relies solely on a cross-sectional design with self-reported questionnaire data, which precludes causal inference. Other factors such as financial literacy, trust, and habits were not included. Contributions: This study contributes empirical evidence on BNPL usage behavior among Generation Z in Indonesia, extending the TPB framework by integrating materialism as an additional predictor and examining mediation through intention, thereby offering novel evidence that materialism can act as a deterrent rather than a driver of debt-based payment usage.